Evaluating the quality of medical and therapeutic services in Iraqi hospitals: an exploratory study of the opinions of a sample of patients in the city of Karbala - Ali Abdul Hussein Jaber Aljas (Iraqi Journal for Administrative Sciences, 2025)
The research aimed to evaluate the efficiency of medical services provided to patients and visitors in hospitals in the city of Karbala by adopting a questionnaire form distributed to patients and visitors in order to survey their opinions. The quality of medical service provided to patients visiting government hospitals in Karbala. The research used a ready-made scale consisting of six elements: information services, nursing services, food services, doctors’ services, hotel services, and support services. The research reached several conclusions, the most important of which was the weak quality of medical and therapeutic services and their failure to live up to the level of ambition of patients and visitors in general in the hospitals in the research sample. The research suggested several recommendations, the most important of which was the need to improve the quality of medical and administrative staff working in hospitals, as well as providing infrastructure and equipment. And therapeutic and service supplies to improve and develop the quality of performance.